Analysis of risk factors for pulmonary tuberculosis with persistent severe inflammation: An observational study. Issue 19 (13th May 2022) - Shimoda, Masafumi; Yoshiyama, Takashi; Okumura, Masao; Tanaka, Yoshiaki; Morimoto, Kozo; Kokutou, Hiroyuki; Osawa, Takeshi; Furuuchi, Koji; Fujiwara, Keiji; Ito, Koki; Yoshimori, Kozo; Ohta, Ken
Abstract: Introduction: Patients with pulmonary tuberculosis (TB) sometimes show persistent severe inflammation for more than 1 month, even if TB treatment is effective. Although this inflammation can be improved through continuous antituberculous therapy, the risk factors for persistent inflammation remain unclear. Therefore, we sought to study the characteristics of patients with persistent severe inflammation. Materials and methods: We retrospectively analyzed 147 hospitalized adult patients with C-reactive protein (CRP) levels of 5 mg/dL or more on admission to Fukujuji Hospital from April 2019 to March 2021. The patients were divided into 2 groups: 40 patients (27.2%) had CRP levels of 5 mg/dL or more at 4 weeks after admission (persistent inflammation group), and 107 patients (72.8%) had CRP levels that fell below 5 mg/dL within 4 weeks of admission (improved inflammation group). Results: The median CRP level on admission in the persistent inflammation group was 10.8 mg/dL (interquartile range 9.1–14.5), which was higher than that in the improved inflammation group (median 8.2 mg/dL [6.5–12.1], P  = .002). Patients in the persistent inflammation group had a higher prevalence of large cavities, defined as cavities ≥4 cm in diameter, on chest computed tomography (CT) (n = 20 [50.0%] vs n = 12 [11.2%], P  < .001). Discussion and conclusions: This study showed that 27.2% of patients who had high or moderate inflammation on admission did not achieve low CRP levels within 4 weeks after admission. Risk factors for persistent severe inflammation in patients with TB were presence of a large cavity (cavity diameter ≥4 cm) on chest CT and a high CRP level on admission. Therefore, in a patient with a large cavity on chest CT and/or CRP ≥9.0 mg/dL on admission, long-term inflammation may occur despite antituberculous therapy if other diseases are ruled out.